Phenomenology of delirium: Assessment of 100 adult cases using standardised measures - MEAGHER, DAVID J; MORAN, MARIA; RAJU, BANGARU; GIBBONS, DYMPNA; DONNELLY, SINEAD; SAUNDERS, JEAN; TRZEPACZ, PAULA T (British journal of psychiatry, 2007)
Delirium phenomenology is understudied. To investigate the relationship between cognitive and non-cognitive delirium symptoms and test the primacy of inattention in delirium. People with delirium (n=100) were assessed using the Delirium Rating Scale-Revised-98 (DRS-R98) and Cognitive Test for Delirium (CTD). Sleep-wake cycle abnormalities and inattention were most frequent, while disorientation was the least frequent cognitive deficit. Patients with psychosis had either perceptual disturbances or delusions but not both. Neither delusions nor hallucinations were associated with cognitive impairments. Inattention was associated with severity of other cognitive disturbances but not with non-cognitive items. CTD comprehension correlated most closely with non-cognitive features of delirium. Delirium phenomenology is consistent with broad dysfunction of higher cortical centres, characterised in particular by inattention and sleep-wake cycle disturbance. Attention and comprehension together are the cognitive items that best account for the syndrome of delirium. Psychosis in delirium differs from that in functional psychoses.